Endophytic Actinobacteria and the Interaction of Micromonospora and Nitrogen Fixing Plants - Trujillo, Martha E.; Riesco, Raúl; Benito, Patricia; Carro, Lorena (Frontiers in Microbiology, 2015)
For a long time, it was believed that a healthy plant did not harbor any microorganisms within its tissues, as these were often considered detrimental for the plant. In the last three decades, the numbers of studies on plant microbe-interactions has led to a change in our view and we now know that many of these invisible partners are essential for the overall welfare of the plant. The application of Next Generation Sequencing techniques is a powerful tool that has permitted the detection and identification of microbial communities in healthy plants. Among the new plant microbe interactions recently reported several actinobacteria such as Micromonospora are included. Micromonospora is a Gram-positive bacterium with a wide geographical distribution; it can be found in the soil, mangrove sediments, and freshwater and marine ecosistems. In the last years our group has focused on the isolation of Micromonospora strains from nitrogen fixing nodules of both leguminous and actinorhizal plants and reported for the first time its wide distribution in nitrogen fixing nodules of both types of plants. These studies have shown how this microoganism had been largely overlooked in this niche due to its slow growth. Surprisingly, the genetic diversity of Micromonospora strains isolated from nodules is very high and several new species have been described. The current data indicate that Micromonospora saelicesensis is the most frequently isolated species from the nodular tissues of both leguminous and actinorhizal plants. Further studies have also been carried out to confirm the presence of Micromonospora inside the nodule tissues, mainly by specific in-situ hybridization. The information derived from the genome of the model strain, Micromonospora lupini, Lupac 08, has provided useful information as to how this bacterium may relate with its host plant. Several strategies potentially necessary for Micromonospora to thrive in the soil, a highly competitive and rough environment, and as an endophytic bacterium with the capacity to colonize the internal plant tissues which are protected from the invasion of other soil microbes were identified. The genome data also revealed the potential of M. lupini Lupac 08 as a plant growth promoting bacterium. Several loci involved in